Acute Effect of Different Stretching Protocols on Fexibility, Yoyo IR-1 and RepeatedSprint Ability Performance - Fahri Safa Çınarlı; Yalçın Aydın; Muhammed Emin Kafkas; Özgür Eken; Armağan Şahin Kafkas (Türk Spor ve Egzersiz Dergisi)
The purpose of this study was to examine the acute effect of different stretching protocols on flexibility, Yo-Yo IR-1 and repeated sprint performance. The sample group of this study consists of 15 male (age: 21.80±1.37 years, stature: 1.77±.032 cm, body mass: 69.09±6.65 kg, body mass index (BMI) 21.94±2.01 (kg/m2), body fat ratio (BFR) 10.87±3.98 (%)) who were doing regular exercise at least 3 years. This group performed 5 different stretching protocols on non-consecutive days. Stretching protocols were determined as follows: light jogging for only 5 minutes (NS), light jogging and static strectching (SS), light jogging and dynamic stretching (DS), light jogging and static + dynamic stretching (SDS), light jogging and dynamic + static stretching (DSS). Altough participants did not have a statistically significant effect on flexibility performance (p gt; 0.05), the best flexibility value was SS. Repeated sprint performance (best) values ​​of different stretching protocols did not have statistically significant effect on repeated sprint performance (moderate, worst, decline, post fatigue index) values (p gt; 0.05). Repeated sprint performance was found to have a statistically significant effect on Borg values ​​and HR mean values ​​(p lt;0.05). It was found that Yo-Yo IR-1 has a statistically significant effect on BORG values, Yo-Yo IR-1 performance HR (pre) values, Yo-Yo IR-1 performance HR (middle) values ​​and Yo-Yo IR-1 performance lactate values (p lt;0.05). According to the findings obtained as a result of the research; it has been observed that different stretching protocols have different effects in terms of repeated sprint, flexibility and Yo-Yo IR-1 performance parameters. Overall, these results suggest that flexibility performance may be improve after static stretching exercise.